Recent progress and remaining hurdles toward clinical xenotransplantation. (23rd March 2021) - Meier, Raphael P.H.; Longchamp, Alban; Mohiuddin, Muhammad; Manuel, Oriol; Vrakas, Georgios; Maluf, Daniel G.; Buhler, Leo H.; Muller, Yannick D.; Pascual, Manuel
Abstract: Background: Xenotransplantation has made tremendous progress over the last decade. Methods: We discuss kidney and heart xenotransplantation, which are nearing initial clinical trials. Results: Life sustaining genetically modified kidney xenografts can now last for approximately 500 days and orthotopic heart xenografts for 200 days in non‐human primates. Anti‐swine specific antibody screening, preemptive desensitization protocols, complement inhibition and targeted immunosuppression are currently being adapted to xenotransplantation with the hope to achieve better control of antibody‐mediated rejection (AMR) and improve xenograft longevity. These newest advances could probably facilitate future clinical trials, a significant step for the medical community, given that dialysis remains difficult for many patients and can have prohibitive costs. Performing a successful pig‐to‐human clinical kidney xenograft, that could last for more than a year after transplant, seems feasible but it still has significant potential hurdles to overcome. The risk/benefit balance is progressively reaching an acceptable equilibrium for future human recipients, e.g. those with a life expectancy inferior to two years. The ultimate question at this stage would be to determine if a "proof of concept" in humans is desirable, or whether further experimental/pre‐clinical advances are still needed to demonstrate longer xenograft survival in non‐human primates. Conclusion: In this review, we discuss the most recent advances in kidney and heart xenotransplantation, with a focus on the prevention and treatment of AMR and on the recipient's selection, two aspects that will likely be the major points of discussion in the first pig organ xenotransplantation clinical trials.